Selected Papers from IEEE ICKII 2018 - Zhao, Wenbing (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Electronic engineering and design innovation are both academic and practical engineering fields that involve systematic technological materialization through scientific principles and engineering designs. Technological innovation via electronic engineering includes electrical circuits and devices, computer science and engineering, communications and information processing, and electrical engineering communications. The Special Issue selected excellent papers presented at the International Conference on Knowledge Innovation and Invention 2018 (IEEE ICKII 2018) on the topic of electronics and their applications. This conference was held on Jeju Island, South Korea, 23-27 July 2018, and it provided a unified communication platform for researchers from all over the world. The main goal of this Special Issue titled "Selected papers from IEEE ICKII 2018" is to discover new scientific knowledge relevant to the topic of electronics and their applications.